Citation classics in neurointerventional research: a bibliometric analysis of the 100 most cited articles. (28th April 2016) - Kim, Eun Soo; Yoon, Dae Young; Kim, Hye Jeong; Jeon, Hong Jun; Lee, Jong Young; Cho, Byung-Moon; Lee, Kwanseop
Abstract : Background and purpose: The number of citations that an article has received can be used to evaluate its impact on the scientific community. This study aimed to identify the 100 most cited articles in the field of neurointervention and to analyze their characteristics. Materials and methods: We selected the 669 journals that were considered potentially to publish neurointervention articles based on the database of Journal Citation Reports. Using the Web of Science citation search tool, we identified the 100 most cited articles relevant to neurointervention within the selected journals. Each article was evaluated for several characteristics including publication year, journal, journal category, impact factor, number of citations, number of citations per year, authorship, department, institution, country, type of article, and topic. Results: The number of citations for the top 100 articles ranged from 1912 to 170 (mean 363.4) and citations per year ranged from 271.0 to 4.1 (mean 40.0). The majority of articles were published in clinical neurology journals (63%), were published in 2000–2009 (39%), originated in the USA (45%), were original articles (95%), and dealt with endovascular treatment of cerebral aneurysm (42%). The Department of Radiology, University of California School of Medicine (n=12) was the leading institution and Viñuela F (n=11) was the most prolific author. Conclusions: Our study presents a detailed list and analysis of the 100 most cited articles in the field of neurointervention and provides a historical perspective on the scientific progress in this field.